Liquid-Phase Selective Oxidation of Methane to Methane Oxygenates - Kang, Jongkyu; Park, Eun Duck (Catalysts, 2024)
Methane is an abundant and relatively clean fossil fuel resource; therefore, its utilization as a chemical feedstock has a major impact on the chemical industry. However, its inert nature makes direct conversion into value-added products difficult under mild conditions. Compared to the gas-phase selective oxidation of methane, there have been several recent advances in the liquid-phase conversion of methane. This review categorizes the reports on the liquid-phase selective oxidation of methane according to the solvent and oxidant used. The advantages and disadvantages of each approach are discussed. High yields of methyl bisulfate as a methanol precursor can be achieved using SO3 in sulfuric acid; however, more attention should be paid to the separation process and overall economic analysis. However, the aqueous-phase selective oxidation of methane with in situ generated H2O2 is quite promising from an environmental point of view, provided that an economical reducing agent can be used. Based on the current state-of-the-art on this topic, directions for future research are proposed.
Keywords: catalyst; formic acid; liquid-phase oxidation; methane; methane oxygenates; methanol; selective oxidation